The conservation of the white cattle of Taro as a representation of Prāṇī-Dharma values, biodiversity preservation, and religious heritage - Rahayu, Ni Wayan Sri; Joyo, Puspo Renan; Binawati, Ni Wayan Sariani (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: The breeding of white cattle in Taro Village, Bali, is not merely an agricultural or economic activity, but one deeply intertwined with spiritual values rooted in the concept of Prāṇī-Dharma. In this context, white cattle are revered not only as symbols of prosperity and wealth, but also as sacred beings that embody harmony between humans and nature. This study aims to explore how the breeding of white cattle in Taro functions as a representation of Prāṇī-Dharma values, particularly in relation to the preservation of tradition and ecology. Methods: Employing a qualitative case study approach, this research involved in-depth interviews with breeders, religious figures, and local community members, as well as field observations of rituals and cattle-rearing practices. The data were analyzed thematically to identify the connections between Hindu spiritual concepts and the practice of white cattle breeding. Finding: The findings reveal that the breeding of Taro’s white cattle reflects an integration of spiritual and ecological dimensions within the local community. The white cattle are regarded as symbols of purity and environmental balance, protected through the principles of Ahimsa (non-violence) and Karuṇā (compassion), which lie at the heart of Prāṇī-Dharma. This practice also plays a vital role in the conservation of living beings and the preservation of local cultural traditions. Conclusion: The study concludes that the breeding of white cattle in Taro is not only a conservation practice but also a means of reinforcing moral and spiritual values within Hindu society. This research contributes to the understanding of the relationship between divine ecology and traditional conservation, enriching the discourse on how religion and local culture support environmental sustainability. Novelty/Originality of this article: The uniqueness of this study lies in the placement of white cattle breeding in Taro as an applied model of Prāṇī-Dharma, which shows how spiritual ethics directly influence conservation practices.